Dependence of some plasma parameters on ap in a dc helium hollow cathode discharge - Chin, Oi Hoong; Wong, C.S. (2002)
The dependence of the electron temperature, electron density and plasma potential of a dc helium hollow cathode discharge with the product of the hollow cathode diameter and gas pressure ap is investigated. These are then compared with reported works and correlated to the optimum pressure range in which the hollow cathode effect is said to be fully developed.